1996
DOI: 10.1007/s002940050030
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Gelasinospora linear plasmid closely related to the kalilo plasmid of Neurospora intermedia

Abstract: We have determined the complete nucleotide sequence of a linear mitochondrial plasmid from a natural isolate of a homothallic species of Gelasinospora. The plasmid genome is 8231 bp long. It carries terminal inverted repeats of 1137 bp. Extending inwards from the terminal repeats are two long open reading frames coding for putative proteins with similarity to DNA and RNA polymerases. These are separated by a short intergenic region. The plasmid sequence shows remarkable similarity to that of the Neurospora int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…This suggests the independent replication of these plasmids, and relates to their very high frequency of distribution in natural populations. The widespread incidence of L. edodes plasmids suggests that they may be neutral genetic elements for their hosts, in contrast to the exceptional case of the kalilo plasmid of Neurospora species, which reduces its incidence in populations through its destructive effect on hosts (Arganoza et al, 1994;Debets et al, 1995;Yuewang et al, 1996). The finding that two L. edodes reciprocal dikaryons with the same nuclei but different plasmid types showed similar morphological properties also supports this idea.…”
Section: Discussionsupporting
confidence: 63%
“…This suggests the independent replication of these plasmids, and relates to their very high frequency of distribution in natural populations. The widespread incidence of L. edodes plasmids suggests that they may be neutral genetic elements for their hosts, in contrast to the exceptional case of the kalilo plasmid of Neurospora species, which reduces its incidence in populations through its destructive effect on hosts (Arganoza et al, 1994;Debets et al, 1995;Yuewang et al, 1996). The finding that two L. edodes reciprocal dikaryons with the same nuclei but different plasmid types showed similar morphological properties also supports this idea.…”
Section: Discussionsupporting
confidence: 63%
“…The latter authors did not report whether this particular isolate showed senescence or not. Several homologues of pKALILO were found in a range of diVerent hosts, including Neurospora discreta, N. crassa, and even in the related genus Gelasinospora (He et al, 2000;Marcinko-Kuehn et al, 1994;Yuewang et al, 1996), but all of these plasmids were substantially diVerent from pKALILO at the DNA sequence level and, in contrast to the prototypic plasmid from N. intermedia, those tested neither integrated into the mitochondrial genome nor showed a convincing correlation with senescence. Thus, Kalilo itself has formally never been described in natural populations of Neurospora outside the Hawaiian one of N. intermedia.…”
Section: Introductionmentioning
confidence: 59%
“…Three of these subtypes were present in strains belonging to four Neurospora species from Hawaii, Tahiti, Thailand, Ivory Coast, Haiti, and Louisiana (He et al, 1997(He et al, , 2000. The fourth was from a strain of Gelasinospora, a genus closely related to Neurospora (Yuewang et al, 1996). Introgression and subsequent heterokaryosis have been used to transfer pKALILO in both directions between N. crassa and N. tetrasperma (Bok et al, 1999).…”
Section: Other Laboratory Investigations Using Naturally Occurring Vamentioning
confidence: 97%